Higher education in chemoinformatics: achievements and challenges - Varnek, Alexandre; Marcou, Gilles; Horvath, Dragos (Journal of cheminformatics, 2025)
While chemoinformatics is a well-established scientific field, its integration into university curricula is rarely discussed. In this work, we share our experience in developing a chemoinformatics curriculum at the University of Strasbourg and highlight the main challenges in higher education for this discipline.